Peran Guru Pendidikan Agama Islam di Era Society 5.0 dalam Membentuk Karakter Siswa - Aziz, Abdul; Salim, Salim; Sy, Syamhadi; Ramadhani, Awalia (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study aims to analyze and describe several key aspects, namely: (1) the role of Islamic Religious Education teachers in facing the challenges and opportunities of education in the society 5.0 era; (2) the forms of innovative learning methods developed; (3) the impact of these innovations on student character formation; (4) obstacles faced by teachers in the implementation process; and (5) effective strategies that can support teachers in implementing learning innovations oriented towards strengthening character. This study employs a qualitative case study approach to gain an in-depth understanding of the innovation practices of Islamic Religious Education teachers. Data were collected through in-depth interviews, participant observation, and documentation. Data analysis was conducted using thematic analysis, which involved data reduction, data presentation, coding, theme identification, interpretation, and drawing conclusions. Data validity was strengthened through triangulation of techniques and sources, member checks, and extended observations. The results of the study indicate that Islamic Religious Education teachers have a strategic role as moral agents, role models (uswah hasanah), and innovators. Various methods, such as digital, blended, experiential, and project-based learning, have a positive impact on student character. However, teachers still face limitations in facilities, digital literacy, and technological distractions. Therefore, a holistic strategy is needed through selecting the right media, strengthening values, increasing competencies, and collaborating with various parties.